Impact of introducing endovascular treatment on acute ischemic stroke outcomes: A shift from an era of medical management to thrombectomy in Japan. Issue 5 (May 2020) - Imahori, Taichiro; Koyama, Junji; Tanaka, Kazuhiro; Okamura, Yusuke; Arai, Atsushi; Iwahashi, Hirofumi; Mori, Tatsuya; Yokote, Akiyoshi; Matsushima, Kazushi; Matsui, Daisaku; Kobayashi, Makoto; Hosoda, Kohkichi; et al.
Abstract: Background: Endovascular treatment (EVT) has increasingly become the standard treatment of acute cerebral large vessel occlusion (LVO). We evaluated the impact of introducing EVT on LVO therapy in a single center where intravenous thrombolysis (IVT) had been the only recanalization therapy. Materials and methods: Between April 2013 and March 2017, 354 consecutive patients with LVO admitted to our institution were analyzed. We compared outcomes between two chronological groups before (Pre-EVT group) and after (Post-EVT group) introducing EVT in April 2015. We assessed prognostic factors for favorable outcomes (modified Rankin scale score ≤2 at 90 days). Results: In the Pre-EVT group, all 140 patients were treated medically, including 30 patients (21%) undergoing IVT. In the Post-EVT group, 118 patients (55%) underwent EVT, and the remaining 96 patients treated medically, including six patients (3%) undergoing IVT. The proportion undergoing recanalization therapy with IVT or EVT significantly increased after introducing EVT (21% versus 58%, p < 0.001). The rate of patients achieving favorable outcomes also significantly increased (14% versus 31%, p < 0.001). In multivariate regression analysis, introducing EVT was an independent predictive factor after adjusting for age, stroke severity and extent, and time (p = 0.005). The arrival time in patients with helicopter transport was significantly shorter than that with ground ambulance for a distance of more than 10 km (p < 0.001). Conclusions: This study demonstrated that the introduction of EVT improved outcomes of acute LVO patients, increasing the opportunity to receive recanalization therapy. Further efforts to establish medical systems to provide EVT are required throughout the country. Abstract : Neurology; Neurosurgery; Emergency medicine; Internal medicine; Radiology; Clinical research; Acute ischemic stroke; Large vessel occlusion; Endovascular treatment; Mechanical thrombectomy; Intravenous thrombolysis; Helicopter transport.